Conducting polymer thin films as substrates for cell cultures. Issue 1624 (2014) - Marzocchi, Marco; Scavetta, Erika; Zironi, Isabella; Castellani, Gastone; Bonfiglio, Annalisa; Malliaras, George G.; Owens, Roisin M.; Fraboni, Beatrice
ABSTRACT: In biological applications, conjugated polymers offer many advantages compared to inorganic semiconductors, due to their favorable electrical properties and their biocompatibility. Many different parameters affect the cell-substrate interaction and in this work we focus our attention on the role played by the oxidation state and surface morphology of conducting polymer substrates. We realized cell culture substrates using a thin film of a biocompatible conducting polymer widely employed in organic electronics, poly(3, 4-ethylene dioxythiophene) doped with poly(styrenesulfonate) (PEDOT:PSS). The oxidation state of the samples was electrochemically modified through the application of a fixed potential, and they were subsequently characterized by atomic force microscopy and optical spectroscopy. Using these techniques we have been able to measure the oxidation state of the polymer films, and to asses that its surface roughness does not depend on its oxidation state. Furthermore, human dermal fibroblast (hDF) were grown on PEDOT:PSS films with different oxidation state, in order to test their efficacy as cell culture substrates and their biocompatibility.